2019
DOI: 10.1002/1873-3468.13681
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cell reprogramming and the hope for a universal blood product

Abstract: Edited by Catherine RobinHaematopoietic stem cells (HSCs) are the only adult stem cells with a demonstrated clinical use, even though a tractable method to maintain and expand human HSCs in vitro has not yet been found. Owing to the introduction of transplantation strategies for the treatment of haematological malignancies and, more recently, the promise of gene therapy, the need to improve the generation, manipulation and scalability of autologous or allogeneic HSCs has risen steeply over the past decade. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 117 publications
(234 reference statements)
0
5
0
Order By: Relevance
“…In 2010, Szabo et al converted human neonatal and dermal fibroblasts into multilineage blood progenitors by inducing ectopic OCT4 expression of the fibroblasts-derived CD45+ cells, promoting the transdifferentiation results from unipotent to multipotent [77]. After then, new strategies in the generation of hematopoietic progenitors emerged and were gradually optimized by either combining various transcription factors [78,79] or facilitated with miRNA [80]. Szabo et al also showed the in vivo engraftment capacity of these fibroblasts-derived blood progenitors comparable to that of umbilic blood and mobilized peripheral bloodderived progenitors.…”
Section: Current Progress Of Transdifferentiationmentioning
confidence: 99%
“…In 2010, Szabo et al converted human neonatal and dermal fibroblasts into multilineage blood progenitors by inducing ectopic OCT4 expression of the fibroblasts-derived CD45+ cells, promoting the transdifferentiation results from unipotent to multipotent [77]. After then, new strategies in the generation of hematopoietic progenitors emerged and were gradually optimized by either combining various transcription factors [78,79] or facilitated with miRNA [80]. Szabo et al also showed the in vivo engraftment capacity of these fibroblasts-derived blood progenitors comparable to that of umbilic blood and mobilized peripheral bloodderived progenitors.…”
Section: Current Progress Of Transdifferentiationmentioning
confidence: 99%
“…red blood cells, platelets, megakaryocytes, Tcells) from pluripotent stem cells or somatic cells, through reprogramming or transgene free protocols, is achievable (159). Reprogramming by (transient) expression of transcription factors is also a very promising strategy to generate HSC-like cells in vitro since a decade (11,(160)(161)(162)(163)(164)(165)(166). However, these HSC-like cells are produced at a very low yield and remain limited in their capacities to self-renew and/or to replenish all blood lineages, which is an absolute requirement for therapeutic use.…”
Section: Recapitulating the Endogenous Hsc Niche In 3d-culture Systems To Produce Bona Fide Hscs And Other Blood Forming Cellsmentioning
confidence: 99%
“…The increased number of diseases and disorders treated at least in part by HSC transplantations and the difficulties to find HSCs with the best donor-patient compatibility is a major issue. Decades of efforts to develop culture conditions, either to expand HSCs ex vivo or to generate new HSCs in vitro, hold great promise but success remains limited (10)(11)(12)(13). The low production of HSC-like cells with limited multilineage and/or self-renewal properties remains a major barrier to a successful use of HSCs for transplantation and gene modification.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue of FEBS Letters entitled 'Neural and Hematopoietic Stem Cell Reprogramming', we present a collection of peer-reviewed original articles and reviews authored by select international experts. They discuss the most exciting recent developments in the field, focusing on hematopoietic [1][2][3][4][5] and neural [6][7][8][9][10] (stem) cell generation/reprogramming in vitro. The future research directions and the obstacles ahead are also put into perspective.…”
mentioning
confidence: 99%
“…In short, Chen et al [1] discuss the recent progress in blood cell reprogramming and the potential use of these cells for disease modeling and therapeutic development; Dur an et al [2] compare and discuss the reprogramming methods used to generate hematopoietic stem and progenitor cells; Daniel et al [3] describe an improved human hemogenic induction protocol for establishing an in vitro model of human hematopoiesis, which may facilitate disease modeling and provide a basis for a platform for cell-based therapeutics; Hansen et al [4] discuss the derivation of erythroid, megakaryoid, and myeloid cells from iPSCs and the obstacles currently hindering therapeutic use; Menegatti et al [5] review the complex transcriptional network regulating blood cell generation during embryonic development and how this information can help in generating these cells in vitro; Traxler et al [6] report the most recent advances in direct induced neural (iN) conversion and compare this to other reprogramming-based neural cell models; Greiner et al [7] highlight the implications of sex-related intrinsic mechanisms and different adult stem cell populations (e.g., mesoderm-derived stem cells, neural stem cells, neural crest-derived stem cells) for stem cell differentiation and regeneration and for the design of new treatment options; Erharter et al [8] discuss different approaches to generate induced neural stem cells (iNSCs) and their promising use for disease modeling, autologous cell therapy, and personalized medicine; Birtele et al [9] report that adding neuronal-specific microRNAs into different culture media improves neuronal maturation and the acquisition of electrophysiological properties during direct neural reprogramming; and finally, Denoth-Lippuner and Jessberger [10] take a broader perspective discussing how reprogramming might lead to the rejuvenation of a cell, an organ, or even the whole organism.…”
mentioning
confidence: 99%